SAE Technical Paper Series 2019
DOI: 10.4271/2019-24-0237
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Ammonia in a Modern Spark-Ignition Engine

Abstract: Ammonia is now recognized as a very serious asset in the context of the hydrogen energy economy, thanks to its non-carbon nature, competitive energy density and very mature production, storage and transport processes. If produced from renewable sources, its use as a direct combustion fuel could participate to the flexibility in the power sector as well as help mitigating fossil fuel use in certain sectors, such as long-haul shipping. However, ammonia presents unfavorable combustion properties, requiring furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…Ammonia is difficult to use directly in internal combustion engines due to the insufficiently fast flame spread, but it is possible. 11,12 In a compression ignition (CI) engine, ammonia may be co-combusted with conventional engine fuel (DF). Two supply systems are used in this solution, one for DF supplied to the engine cylinder and the other for alternative fuel, supplied most often to the intake manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia is difficult to use directly in internal combustion engines due to the insufficiently fast flame spread, but it is possible. 11,12 In a compression ignition (CI) engine, ammonia may be co-combusted with conventional engine fuel (DF). Two supply systems are used in this solution, one for DF supplied to the engine cylinder and the other for alternative fuel, supplied most often to the intake manifold.…”
Section: Introductionmentioning
confidence: 99%
“…From this review, it is striking to realize that only a few have explored the feasibility of running an SI engine with ammonia only. At this state it can be concluded that pure ammonia is possible mainly at full load operation, as underlined in [22] and recently confirmed by Lhuillier et al [24,25]. To improve the combustion process, the best carbon-free promoter is hydrogen but also due to its combustion velocity and wide flammability range.…”
Section: Introductionmentioning
confidence: 69%
“…About half of them were conducted in CFR engine with CR ranging from 6.1 to 10, which is representative of current vehicles [6,10,[17][18][19][20][21]. The other half were conducted with modern single cylinder engine [22][23][24][25] or multi-cylinder engine [26,27]. Among those studies, only two investigated higher CR, i.e., about 14:1 [6,22].…”
Section: Introductionmentioning
confidence: 99%
“…Others report RON of over 130 when lean mixtures are used. When the intake is at atmospheric temperature hydrogen shows a very high RON, enabling compression ratios (CR) higher than 14.5:1 without knock, probably helped by its very high combustion velocities [53].…”
Section: Hydrogenmentioning
confidence: 99%
“…Supercharging seems to be a good option [102] and some researchers used plasma ignition with good results [103]. As one of the major problems is its slow combustion, engine conditions of low charge and high speed can only be achieved using a combustion "promotor" such as hydrogen [53], petrol or even diesel fuel, enabling a better ignibility and increased combustion velocity. It can be burned in CI engines when mixed with diesel, but it would be advantageous to be mixed with biodiesel or DME as these fuels have higher cetane numbers (CN) [104].…”
Section: Ammoniamentioning
confidence: 99%